2007
DOI: 10.1136/thx.2005.056036
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards screening for lung cancer among smokers and their non-smoking counterparts

Abstract: Background: There has been resurgence of interest in lung cancer screening using low-dose computed tomography. The implications of directing a screening programme at smokers has been little explored. Methods: A nationwide telephone survey was conducted. Demographics, certain clinical characteristics and attitudes about screening for lung cancer were ascertained. Responses of current, former and never smokers were compared. Results: 2001 people from the US were interviewed. Smokers were significantly (p,0.05) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(131 citation statements)
references
References 25 publications
10
118
3
Order By: Relevance
“…Silvestri et al 92 reported that smokers perceived fewer benefits and were less likely to consider lung cancer screening than non-smokers. Non-participants in NELSON 88 were more likely to be female and former smokers, and to have a lower perceived risk of lung cancer and less-positive beliefs about the benefits of lung screening than participants.…”
Section: Barriers To Uptake Of Lung Cancer Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Silvestri et al 92 reported that smokers perceived fewer benefits and were less likely to consider lung cancer screening than non-smokers. Non-participants in NELSON 88 were more likely to be female and former smokers, and to have a lower perceived risk of lung cancer and less-positive beliefs about the benefits of lung screening than participants.…”
Section: Barriers To Uptake Of Lung Cancer Screeningmentioning
confidence: 99%
“…These findings are consistent with barriers to uptake reported in previous lung screening studies, including female gender, 100 perceived threat associated with lung cancer and lung screening tests, 95,96 and low perceived benefit among smokers. 92 Individuals from more affluent backgrounds may have a better understanding of the benefits of screening and face fewer barriers than those from poorer backgrounds. 101 Furthermore, these groups continued to be under-represented as the trial progressed, with greater attrition seen in women, smokers, less affluent individuals, those from the Liverpool area and those with higher baseline psychosocial scores.…”
Section: Trial Non-uptakementioning
confidence: 99%
“…This is likely to be much more evident in real life in comparison to a highly motivated volunteer population. It has been shown that smokers in the USA are significantly more likely than never smokers to be male, non-white and less educated; to report poor health status; and to be less likely to be able to identify a usual source of healthcare [21]. This study also indicated that current smokers were less likely than never smokers to believe that early detection would result in a good chance of survival and expressed relative reluctance to consider computed tomography screening for lung cancer.…”
Section: Downsides Of Ldct Screeningmentioning
confidence: 51%
“…Two studies have assessed the potential make-up of the screening population. The first found that smokers were significantly more likely than never smokers to report poor health status and less likely to be willing to consider CT screening for lung cancer (11). The second study found that self-selected screening participants were younger, more frequently current smokers, had more pack-years of smoking, and had a higher rate of a family history of lung cancer and of occupational lung cancer risk relative to nonparticipants (12).…”
Section: Original Researchmentioning
confidence: 83%